ISOLATION AND IDENTIFICATION OF BACTERIA ASSOCIATED WITH DECOMPOSING PIG (Sus scrofa) CARCASS - Olatubi, Iyabo Victoria; Aromolaran, Olukemi; Joseph, Samuel Tolani; Adeleke, Oluwafeyikemi Ajoke (Bacterial Empire, 2021)
The emerging field of forensic biology has attempted to solve certain problems encountered when estimating post-mortem interval (PMI) by using predictable changes in the microbial and arthropod community structure. Pig (Sus scrofa) carcasses are widely used as animal models in clinical human studies. The objective of this study was to identify bacteria from the skin surface of pig carcass for possible use in forensic investigation. Three pigs (a suitable human substitute) were collected from a local farm and killed by suffocation and further place in a bush land for decomposition. 24hours later skin samples were collected and transported to the laboratory for the isolation of bacteria using standard pour plate techniques and identified using Bergey’s manual of systemic bacteriology. The experiment was conducted in February 2019 during the dry season of the year with an average temperature of 23.50c and relative humidity of 60.8% A total of fourteen (14) isolates were gotten from the pig carcass samples out of which four (4) were Gram-positive bacteria and the remaining ten (10) were Gram-negative. Staphylococcus spp. (28.6%) was the most abundant while Salmonella sp., Serratia sp., Klebsiella sp., Citrobacter sp. and Proteus sp. occurred at 14.3% each. This study focus on the type of bacteria communities during a decomposition process which will help provide baseline information in the application of forensic biology to determination of nature of death, abuse or neglect.